Role of Iron Deficiency in Oral Submucous Fibrosis: An Initiating or Accelerating Factor - Ganapathy, K; Gurudath, Shubha; Balikai, Bharati; Ballal, Sushmini; Sujatha, D (Journal of Indian Academy of Oral Medicine and Radiology, 2011)
To estimate the hemoglobin and serum iron levels in patients diagnosed with oral submucous fibrosis and to compare the values with that of the healthy subjects and with patients diagnosed of iron deficiency anemia Patients reporting to the Department of Oral Medicine and Radiology, The Oxford Dental College, Hospital and Research Center, Bengaluru, who were clinically and histopathologically diagnosed with oral submucous fibrosis, were subjected for estimation of hemoglobin and serum iron levels by using Sahli′s method and Ferrene method respectively. Hemoglobin and serum iron levels were low in patients with oral submucous fibrosis when compared with healthy control and a significant reduction in serum iron levels were found in comparison with anemic patients.